Desain And Implementation Framework CI (CODE IGNITER) On Sales Information System CV. Kurnia Mebel - Ahmad Tajuddin; Atus Mita (Journal of International Multidisciplinary Research, 2024)
CV Kurnia MebeI Indah is a furniture industry engaged in the production and sale of household furniture. The existing sales system is still conventional, namely consumers must come directly to the showroom. This can hinder sales for potential customers who are out of town. In addition, the input of customer data, product data, and transaction data is still not stored properly and neatly because it still uses manual paper records. In this study, the authors built a web-based sales application (e-commerce) using the codeigniter framework. The method used in software development is the waterfall method, which in this method, starts from analyzing needs, system and software design, coding, testing, and program implementation. The result of this research is the implementation of a web-based sales system (e-commerce) at CV. Kurnia Mebel, can be used as a means of sales that can be accessed online anywhere and anytime, the purchase process can be done directly without having to come to the showroom, and can facilitate the storage of customer data, products, and company transactions.